The Legislators’ Engagement in Policy-making and Post-legislative Scrutiny in Nepal Since 1991 - Sanjaya Mahato; Rupesh Kumar Sah; Pooja Chaudhary (Jember University Press, 2020)
Parliament enacts legislation and has a role to evaluate the implementation of legislation in meeting the intended outcomes. Post-legislative scrutiny (PLS) identifies defective legislation and rectifies it. As such, it contributes to better legislation and implementation of legislation objectives. However, this requires a strong commitment by the parliamentarians in the legislation process and policymaking. Along with a range of structural factors, including lack of expertise and experience and time constraints, the main reasons for the ineffective post-legislative review in Nepal stem from the Member of Parliaments’ (MPs) shallow engagement in policy-making and legislative review processes and stronger focus on expanding expenditure related to building roads, schools, and other vital infrastructure. For example, the Constituency Development Fund (CDF) provided to MPs has been continuously increased in consecutive elections since 1991. MPs appear to prioritize the political benefits of engaging with their electorate on funding and development projects, over their role in reviewing or scrutinizing legislation. This paper argues that the shallow engagement of MPs in the policy-making process and ineffective post-legislative review has resulted in not only defective and unsustainable policies but also defective legislation. This has created problems in the rule of law and accountability. This paper largely draws from reviewing contributions of delegated legislation committee for rule of law, evaluates the implementation of the committee recommendations in improving legislation and analyse the effects of noncompliance of committees’ recommendations in people’s justice.